Carbon Nanotubes-Based Sensor For Ammonia Gas Detection – An Overview. - Abdullah, Norli; Mohamad, Imran Syakir; N.M., Nurazzi; S.Z.N., Demon; N.A., Halim (Industrial Chemistry Research Institute, 2021)
A sensitive, selective and reliable sensing techniques for ammonia (NH3) gas detection have been highly demanded since NH3 is both a commonly utilized gas in various industrial sectors, and considered as a toxic and caustic agent that can threat human health and environment at a certain level of concentrations. In this article, a brief on the fundamental working principles of sensor specifications of the analytes detection techniques relying has been reviewed. Furthermore, the mechanism of NH3 detection and recent progress in the development of advanced carbon nanotubes (CNTs)-based NH3 gas sensors, and their performance towards the hybridization with the conductive polymers was comprehensively reviewed and summarized. Finally, the future outlook for the development of high performance NH3 sensors was presented in the conclusions part.